Thioureidocalix[6]arenes Pseudorotaxanes. Issue 42 (24th September 2021) - Cera, Gianpiero; Bazzoni, Margherita; Andreoni, Leonardo; Cester Bonati, Federica; Massera, Chiara; Silvi, Serena; Credi, Alberto; Secchi, Andrea; Arduini, Arturo
Abstract: Heteroditopic calix[6]arenes are extensively exploited as synthetic receptors and as molecular components of supramolecular threaded and interlocked structures. We describe the synthesis of two novel calix[6]arene macrocycles, the upper rim of which is functionalized with either two or three phenylthioureido groups. These moieties are excellent hydrogen‐bond donors and largely affect the conformation of the macrocycle, both in solution and in the solid state. Alternate conformers are observed in solution, and they give rise to supramolecular chains in the solid state. Moreover, and because of this conformational freedom, also the recognition properties toward the formation of pseudorotaxanes with bipyridinium‐based axles are strongly affected. The number of phenylthioureido units of the macrocyclic host and the nature of the counterions of the bipyridinium guest determine the stability of the complexes. NMR, UV‐Vis and electrochemical measurements revealed that very stable 1 : 1 inclusion complexes are formed between the triphenylthioureido calix[6]arene and a bipyridinium guest with tosylate counterions, whereas no complex is observed between the diphenylthioureido macrocycle and a hexafluorophosphate bipyridinium salt. Abstract : Two novel calix[6]arene derivatives with phenylthioureido hydrogen‐bond donor (HBD) groups appended at the upper rim were investigated. The number of HBD units affects the conformation of the macrocyclic hosts and their binding abilities towards bipyridinium‐based guests, as a function of their counterions.